3D Exoscope Navigation-Guided Approach to Middle Cranial Fossa. Issue 8 (September 2021) - Kaul, Vivian F.; Fan, Caleb J.; Perez, Enrique; Schwam, Zachary G.; Hadjipanayis, Constantinos; Wanna, George B.
Abstract : Objective: To test the feasibility and efficacy of a 3D exoscope navigation-guided middle cranial fossa (MCF) approach to the internal auditory canal (IAC); to potentially obviate the need to use dissection landmarks and instead, use the navigation probe as a guide to find structures and drill down to the IAC. Patients: Cadaveric dissection of six temporal bones. Intervention: Computed tomography temporal bone was performed with fiducials on each specimen before the dissection to employ the navigation system. Using a 3D exoscope with navigation by Synaptive (Toronto, Ontario, Canada), the MCF approach was performed. Main Outcome Measures: Navigation accuracy, ability to identify critical structures, and ability to drill out the IAC successfully. Results: All six specimens had the IAC successfully drilled out using the 3D exoscope. All dissections were performed with navigation and did not require dissecting out the greater superficial petrosal nerve and superior semicircular canal. One specimen used landmark dissection to confirm the IAC after navigation had been used to locate the IAC first. Navigation accuracy mean was 1.86 mm (range, 1.56–2.05 mm). Conclusion: A 3D exoscope navigation-guided MCF approach to the IAC is feasible without landmark dissection.